Effects of extender composition, cooling rate and freezing on the fertilisation viability of spermatozoa of the Pacific oyster (Crassostrea gigas) - S. IEROPOLI; P. MASULLO; M. DO ESPIRITO SANTO; SANSONE, GIOVANNI (2004)
Abstract The aim of this research was to optimise protocols for freezing spermatozoa of the Pacific oyster. All the phases of the cryopreservation procedure (choice of cryoprotectant, cooling, freezing, and thawing) were studied in relation to the species of spermatozoa to restore on thawing the morphological and physiological characteristics of fresh semen. The choice of type and concentration of cryoprotectant in which semen is incubated before freezing is fundamental for a successful cryopreservation: the cryoprotectants (dimethylsulfoxide—Me2SO, ethylene glycol—EG, propylene glycol—PG, and glycerol in concentrations between 5 and 15%) were tested for their toxicity on the semen exposed up to 30 min at +26 _C (room temperature) by evaluating its ability to fertilise and the embryo development to the regular D larval stage. The best cryoprotectants, Me2SO, EG, and PG 5, 10, and 15% respectively, were used for the pre-cooling (adaptation/cooling) tests. Two different adaptation/cooling procedures were tested: (A) from +26 _C to 0–2 _C (2.6 _C/min) and (B) at +26 _C for 15 min. Lastly, using the cryoprotectants and the adaptation procedure (B) that had given the best results in the preceding stages of the experiment, four cooling rates were tested: 6, 11, 16, and 21 _C/min. It was seen that the semen that was incubated with EG 10%, adapted at +26 _C for 15 min, and then cooled at a rate of 6 _C/min showed a percentage of regular D larvae on thawing comparable to that of fresh semen (p > 0.05).